DEVELOPING TEACHING MEDIA BY USING CANVA FOR WRITING RECOUNT TEXT - Nurul Fadila; Tiarnita Maria Sarjani Br Siregar (Universitas Negeri Medan, 2023)
This study has an objective namely to develop Canva as media in teaching writing Recount Text for tenth grade students of SMAN 11 Medan. Qualitative descriptive method was used in this study. This research was conducted by using six steps of Educational Research and Development (R&D), namely: gathering data, analyzing data, designing media, validating by expert, revising media, and final product. Questionnaire sheet was the instrument used in collecting data. The finding of this research showed that teaching media in form of video which was created by using Canva has been validated by two experts and the average score of four categories: Linguistic Dimension, Process, Product Dimensions and Contents, and Face Dimension / Layout was 90%. It was categorized as excellent score for the developed media Canva of teaching writing Recount Text for tenth grade students of SMAN 11 Medan. Keywords: Research and Development (R&D), Teaching Media Canva, Scientific Approach, Writing Recount Text, Senior High School